2016
DOI: 10.1038/srep26973
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Catalase C262T Gene Polymorphism in the Susceptibility and Survival of Cancers

Abstract: Catalase (CAT), one antioxidant enzyme, may provide resistance against many diseases. Many previous studies reported predictive and prognostic values of CAT C262T polymorphism in cancers, with divergent results. This study aimed to summarize the overall relationships between CAT C262T polymorphism and cancer risk or survival. A total of 27 eligible publications were included in susceptibility analysis, while 8 publications contained survival outcomes. The results revealed significant relationship between CAT C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…In a recent meta-analysis [17] of several studies regarding different cancer types, including hematological ones, it was suggested that the CAT C262T polymorphism may be associated with cancer susceptibility, and even more, may be considered a potential tumor biomarker. Nevertheless, the CAT C262T polymorphism is not considered an accurate prognostic factor for cancer survival rate [17]. According to our results, the CAT C262T is not a risk factor for NHL development, but it was associated with lower overall survival rate in dominant model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis [17] of several studies regarding different cancer types, including hematological ones, it was suggested that the CAT C262T polymorphism may be associated with cancer susceptibility, and even more, may be considered a potential tumor biomarker. Nevertheless, the CAT C262T polymorphism is not considered an accurate prognostic factor for cancer survival rate [17]. According to our results, the CAT C262T is not a risk factor for NHL development, but it was associated with lower overall survival rate in dominant model.…”
Section: Discussionmentioning
confidence: 99%
“…According to SNPedia [15] and NCBI [16], there is a consistent number of single nucleotide polymorphisms (SNPs) of the human catalase gene. In the last few years, there has been a significant number of case-control and meta-analysis studies [17,18] focusing on the CAT C262T polymorphism (substitution of Cytosine with Thymine in the 262 position of the promotor) involved in the progression of neoplasia, but more studies regarding NHL are still needed [10,19].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have showed the role of CAT gene promoter polymorphism in disease susceptibility, especially diseases related to metabolic disorders. 2 , 3 , 4 , 9 CAT -21A/T (rs7943316) gene TT genotype was observed in 80% of T2DM patients along with lower CAT enzyme activity. 10 Cerebral stroke and hypertension patients showed the association of CAT -21A/T (rs7943316) gene polymorphism with increased risk of disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Most of the antioxidant enzyme genes have susceptibility for polymorphism and may contribute in the alteration of gene expressions and decrease the activity of these enzymes. 2 Different metabolic disorders are shown to be associated with the modified antioxidant enzymes functions. 3 Catalase (CAT) is one of the powerful antioxidant enzymes because of its highest turnover rate and exists in almost all aerobically respiring organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variation in CAT have been found to associate with impaired CAT activity and certain diseases [41]. Two common CAT SNPs, rs1001179 and rs794316, were found to be associated with prostate cancer risk and survival [42,43]. So far, there is no riskrelated CAT polymorphisms identified in gastric cancer [44,45].…”
Section: Discussionmentioning
confidence: 99%